A fatal case of malignant posterior reversible encephalopathy syndrome in the setting of status epilepticus: a case report - Ojas Unavane; Tushar Premraj Raut; Lakhan Parajiya; Alisha Rajan Sadarangani (Journal of Neurocritical Care)
Background Posterior reversible encephalopathy syndrome (PRES) is characterized by reversible neurotoxicity. The symptoms include headache, altered consciousness, seizures, visual disturbances, and focal neurological deficits. The severe variant, known as malignant PRES, is rare and involves diffuse cerebral edema, leading to irreversible damage. Chronic kidney disease (CKD) with impaired blood pressure regulation is a known risk factor for malignant PRES. Case report We report the case of a patient with CKD who presented with hypertensive crisis and later developed malignant PRES in the background of status epilepticus refractory to antiepileptic treatment. Conclusions This case highlights the importance of considering malignant PRES in hypertensive crises and emphasizes the need for further research to elucidate its pathophysiology and develop effective treatment strategies.